“The most important thing is that those closest to you, understand you”: a nested qualitative study of persons with psychotic disorders’ experiences with family involvement - Hansson, Kristiane M.; Romøren, Maria; Hestmark, Lars; Heiervang, Kristin Sverdvik; Weimand, Bente; Norheim, Irene; Pedersen, Reidar (Frontiers in Psychiatry, 2023)
Background: Family interventions constitute effective treatment for persons with psychotic disorders. However, the active ingredients and beneficial processes of these interventions are insufficiently examined, and qualitative explorations of patients` experiences are lacking. This study was nested in a cluster randomised trial that implemented national guidelines on family involvement in Norwegian community mental health centres, including family psychoeducation and basic family involvement and support. The aim of this sub-study was to explore how patients with psychotic disorders experience systematic family involvement, and its significance. Methods: We conducted semi-structured, individual interviews with thirteen persons with a psychotic disorder after systematic family involvement. The participants were recruited through purposive sampling. Qualitative content analysis guided the analysis. Results: Participants reported overall positive experiences with systematic family involvement. It was significant that the relatives increasingly understood more about psychosis and their situation, while they themselves also gained more insight into the relatives` situation. The participants emphasised the need to enable both patients and relatives to safely share experiences in a containing space, led by professionals. Shared understanding and awareness of each other’s situation further improved communication, coping with the illness, reduced stress, and stimulated a more caring family environment. The therapist seemed crucial to facilitate these beneficial communication processes, and also to provide continuous support to the relatives. Reported challenges included that the participants felt vulnerable in the initial phase, a need for tailored approaches, and too late start-up. Conclusion: Findings from this study suggest that persons with psychotic disorders may benefit greatly from participating in systematic family involvement. This study also gives new insight into possible mediators of positive outcomes both for the patients and the relatives. Systematic family involvement should probably be implemented a standard approach in the early phase of the disease, using a step-wise and tailored process.